The effect of tax planning and deferred tax expense on earnings management - Herdiansyah, Endra; Septiawan, Budi; Ikhsan, Sugiyanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aimed to analyze the effect of Tax Planning and Deferred Tax Expense to Earnings Management. The independent variable is Tax Planning and Deferred Tax Expense and the dependent variable is the Earnings Management. Data were obtained from the financial statement of 6 manufacturing companies in food and beverages sub-sector listed on Indonesia Stock Exchange in the period 2014-2018. The study uses Multiple Linear Regression Test as the data analysis method. The results show that Tax Planning partially has not a significant positive effect to Earnings Management and Deferred Tax Expense partially have a significant positive effect to Earnings Management. Simultaneously, Tax Planning and Deferred Tax Expense had an effect to Earnings Management.